Leisure activity participation in relation to alcohol purchasing and consumption in adolescence. (March 2019) - Chen, Chuan-Yu; Wang, I-An; Wang, Nadia; Lu, Ming-Chun; Liu, Chieh-Yu; Chen, Wei J.
Abstract: Background: Building upon the socioecological perspective, this study examines prospective associations linking leisure activity participation with alcohol purchasing and consumption in early adolescence. Methods: A total of 1763 seventh graders (age 12–13 years) were recruited from middle schools in urban Taiwan via multi-stage sampling and followed-up 1.5 years later during ninth grade. Information about leisure activities, covariates (i.e., gender, puberty development, family structure, parental educational attainment, monthly allowance, peer drinking, and childhood alcohol experience), and two outcome variables (i.e., alcohol purchasing and drinking behaviors) was gathered via web-based self-administered questionnaires. Data concerning alcohol outlets and recreational resource for each community district were retrieved from official statistics and commercial sources. Two-level hierarchical generalized linear models were used to evaluate association estimates. Findings: Five percent of ninth graders ever purchased alcohol and nearly one in seven drank alcohol on three or more occasions (i.e., occasional drinking) in the past year. Sports, unstructured, and organized leisure activities were not linked with illegal alcohol purchasing when community contexts were statistically adjusted; a higher community on-premised alcohol outlet density increased alcohol purchasing by 94% (95% CI = 1.24–3.06). In contrast, unstructured leisure activity participation at 7th grade predicted occasional drinking (adjusted Odds Ratio [aOR] = 5.52; 95% CI = 3.13–9.74). Sports participation was associated with reduced risk of occasional drinking in the communities with high unregulated alcohol outlets (aOR for interaction = 0.58; P  < .001). Conclusion: Our research provides insights to differential roles of leisure activity participation in shaping adolescents' commercial alcohol access and occasional drinking. Macro-social contexts should be considered in the efforts to reduce underage drinking problems through leisure activities.